(untitled) (Academicia Globe: Inderscience Research, 2023)
This thesis aims to examine the specific features of poetic and prose translation in Uzbek and English languages through a comparative analysis. The study focuses on the challenges and strategies of translating poetry and prose from Uzbek to English and vice versa. The research is based on the analysis of selected literary works from both languages, as well as interviews with professional translators and scholars in the field of translation studies.